Riding the demon : on the road in West Africa - Chilson, Peter (The University of Georgia Press, 2015)
In Niger, where access to rail and air travel requires overcoming many obstacles, roads are the nation's lifeline. For a year in the early 1990s, Peter Chilson traveled this desert country by automobile to experience West African road culture. He crisscrossed the same roads again and again with bush taxi driver Issoufou Garba in order to learn one driver's story inside and out. He hitchhiked, riding in cotton trucks, and traveled with other bush taxi drivers, truckers, road engineers, an anthropologist, Niger's only licensed woman commercial driver, and a customs officer. The road in Africa, s.